Functional Mechanism of Moxibustion and Its Enlightenment to Design and Manufacture of Moxibustion Apparatus - 钟力炜 章家福 苑洁 周春燕 邓琦林 (Journal of acupuncture and tuina science, 2010)
Objective To explore the functional mechanism of moxibustion and its enlightenment to the design and manufacture of moxibustion apparatus. Methods The functional mechanism of moxibustion is explored from its pharmaceutical properties, warming stimulation, spectrum, radiation features, and penetrating effects of moxa products. Result The mechanism of moxibustion is a combined action of moxa’ medicinal properties, warming effect and non-thermal effect. Conclusion It is necessary to combine with the functional mechanism to design and manufacture moxibustion apparatus.